Screening of a test charge in a free‐electron gas at warm dense matter and dense non‐ideal plasma conditions. Issue 2 (24th January 2021) - Moldabekov, Zhandos A.; Dornheim, Tobias; Bonitz, Michael
Abstract: The screening of a test charge by partially degenerate non‐ideal free electrons at conditions related to warm dense matter and dense plasmas is investigated using linear response theory and the local field correction based on ab initio Quantum Monte‐Carlo simulations data. The analysis of the obtained results is performed by comparing to the random phase approximation and the Singwi–Tosi–Land–Sjölander approximation. The applicability of the long‐wavelength approximation for the description of screening is investigated. The impact of electronic exchange‐correlations effects on structural properties and the applicability of the screened potential from linear response theory for the simulation of the dynamics of ions are discussed.